An Impulse Model for Computer Viruses - Chunming Zhang; Yun Zhao; Yingjiang Wu (Discrete Dynamics in Nature and Society)
Computer virus spread model concerning impulsive control strategy is proposed and analyzed. We prove that there exists a globally attractive infection-free periodic solution when the vaccination rate is larger than θ0. Moreover, we show that the system is uniformly persistent if the vaccination rate is less than θ1. Some numerical simulations are finally given to illustrate the main results.